JARINGAN RADIKALISME DI JAWA TIMUR PASCA REFORMASI - Gonda Yumitro; Rizki Febriani; Ali Roziqin; Sukma Oktaviani (Jisiera: The Journal of Islamic Studies and International Relations, 2023)
This article examines the radicalism networks in East Java Post-reformation Indonesia. The explanation focuses on the existence of radicalism groups and its movement that are camouflaged in Indonesian education life since post-reformation. The method used in this article was qualitative research by using some applications such as Harzing Published or Perish to collect data publications, Mendeley to changed data as a RIS, and Vos viewer for visualizing data relevant to the topic and help to compile the explanation in this article. It is found that radicalism in Indonesia was connected to domestic and transnational movements. The result showed Jamaah Ansharut Daulah (JAD) was the most active group radical that carried out acts of terror in East Java. Even today, JAD was known as a dangerous terrorist group, not only in Indonesia but also globally.